Higher Genomic Variation in Wild Than Cultivated Rubber Trees, Hevea brasiliensis, Revealed by Comparative Analyses of Chloroplast Genomes - Feng, Li-Ying; Liu, Jin; Gao, Cheng-Wen; Wu, Hai-Bo; Li, Guo-Hua; Gao, Li-Zhi (Frontiers in Ecology and Evolution, 2020)
Rubber tree is the only commercialized natural resource to produce high-quality natural rubber with unique physical and chemical properties. They currently foster in Southeast Asia with marked morphological and productive differences with wild germplasms native to the Amazonian basin of South America. Here, we report complete chloroplast (cp) genomes of six cultivated and six wild accessions of H. brasiliensis using Illumina paired-end sequencing platform. The twelve H. brasiliensis cp genomes ranged from 161,168 to 161,254 bp. All twelve cp genomes displayed a typical quadripartite structure, which consisted of a pair of IR regions (26,787-26,804 bp) separated by a LSC region (89,216-89,284 bp) and a SSC region (18,370-18,377 bp). Phylogenomic analysis revealed that cultivated and wild rubber trees failed formed separate clades. However, we observed that wild rubber trees possessed more variable sites and ~2.8-fold higher level of nucleotide variation than cultivated rubber trees despite a short domestication history. We drew a comprehensive map of genomic variation across rubber tree plastomes, exhibiting that the density of genomic variants in wild rubber trees was slightly higher than that detected in cultivated ones. The obtainability of genomic variation across cp genomes will provide useful information for better conserving and utilizing rubber tree germplasms.